Money stock control and inflation targeting in Germany : a state space modelling approach to the Bundesbank's operating procedures and intermediate strategy - Brand, Claus (Heidelberg ; New York : Physica-Verlag, 2001)
This work considers issues relevant to the European Central Bank in refining and communicating its strategy. It offers a historical assessment of the Bundesbank's strategy of monetary targeting conducted from 1974 to 1998.
Originally presented as the author's thesis (doctoral)--Universität GH Essen, 1999.
Includes bibliographical references (p. [151]-155).
oif 11/07/14
Loan
Keywords: Deutsche Bundesbank; Inflation targeting; Money stock